THE VIENNA SYSTEM OF INTERNATIONAL RELATIONS AND ITS INFLUENCE ON THE DEVELOPMENT OF MUSEUM BUSINESS IN FRANCE IN THE FIRST HALF OF THE 19TH CENTURY - Юлдашева Ш. Ю. (TARIXIY TADQIQOTLAR, 2026)
This article is devoted to a comprehensive study of the influence of the Vienna system of international Relations, established following the Vienna Congress of 1814-1815, on the development of museum business in France in the first half of the 19th century. The research is based on the study of a wide range of historical sources and scientific literature, which make it possible to trace the transformation of French museum institutions in the post-Napoleonic period. The article examines in detail the process of museum property restitution initiated by the decisions of the Congress of Vienna, which became a turning point in the history of museum business not only in France, but throughout Europe.. Special attention is paid to the activities of such key figures as Dominique Vivandenon, Antonio Canova, as well as the role of Louis Philippe d’orleans in the creation of new museum institutions.